The Georgian star : how William and Caroline Herschel revolutionized our understanding of the cosmos - Lemonick, Michael D., 1953- (New York : Atlas & Co. : W.W. Norton & Co., 2009)
A tribute to the scientific contributions of Uranus planet discoverer William Herschel and his pioneering sister, Caroline, describes their establishment of surveying techniques that are still in use today, Caroline's cataloguing of nebulae, and William's discovery of infrared radiation.
Includes bibliographical references (p. 177-180) and index.
Keywords: Herschel, William, -- 1738-1822.; Herschel, Caroline Lucretia, -- 1750-1848.; Astronomy -- History -- 19th century